2019
DOI: 10.1002/lary.28071
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implant failures and reimplantation: A 30‐year analysis and literature review

Abstract: Objectives/Hypothesis The objectives of the study were to present an institutional experience with device failures and cochlear reimplantation rates over a 30‐year period and to perform a detailed literature review. Study Design Retrospective institutional experience and literature review. Methods A review of cochlear implant failures over a period of 30 years, between January 1988 and March 2017, at a single institution was conducted. Cochlear implant failures were calculated based on manufacturer, type of fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
48
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 31 publications
6
48
3
Order By: Relevance
“…With a follow-up period of eight years, our revision rate of children was 6.7%. This is similar with the revision rate of other studies in literature [1,10,23]. Brown, et al [24] found that the revision rate was higher in pediatric population with 7.3% than adult with 3.8% and also showed that the hard failure was more seen reason with the rate of 55% in their study.…”
Section: Discussionsupporting
confidence: 88%
“…With a follow-up period of eight years, our revision rate of children was 6.7%. This is similar with the revision rate of other studies in literature [1,10,23]. Brown, et al [24] found that the revision rate was higher in pediatric population with 7.3% than adult with 3.8% and also showed that the hard failure was more seen reason with the rate of 55% in their study.…”
Section: Discussionsupporting
confidence: 88%
“…They found that at 10 years post-implantation, almost 30% of children with unilateral implants are expected to undergo RCI. Although this finding considerably exceeded other reported revision rates [ 4 , 34 ], it illustrated the importance of interpreting results with respect to a relevant timeframe. According to our data, the mean time interval between Pri-CI and RCI was 6.6 years, comparable to results of other studies, which reported a mean length of device use before revision of 4.7–6 years [ 4 , 16 , 17 , 35 ].…”
Section: Discussioncontrasting
confidence: 68%
“…In other words, 70% of RCIs were performed in cases having an implant lifetime of less than 10 years. Further analysis, focusing on the time between Pri-CI and the onset of symptoms that led to RCI, revealed a significant prolongation in children compared to adults, presumably related to the unique challenges involved in diagnosing CI failures in the pediatric population [ 34 , 36 ]. Taken together, our results strongly emphasize the need for close monitoring and special attention regarding follow-up of babies and young children, especially during their first years of implant use.…”
Section: Discussionmentioning
confidence: 99%
“…Using minimally invasive surgical techniques and less traumatic devices for inner ear, we can avoid the cochlear and vestibular lesions not only for the first cochlear implantation intervention, but also for the reimplantation purposes, even these cases are not very frequent, as many studies have shown, the CI devices having a very good reliability [36][37][38].…”
Section: Figure 4 -Postoperative Saccular Status (T1) For Bilateral Sequential Versus Bilateral Simultaneous Cochlear Implantation In Chimentioning
confidence: 99%